Cell Surface Expression of 70 KDa Heat Shock Proteins and P21 in Normal Oral Mucosa, Oral Epithelial Dysplasia and Squamous Cell Carcinoma (An Immunohistochemical Study) - Neamah, Ali Shafeeq; Majeed, Ahlam Hameed (Journal of Baghdad College of Dentistry, 2016)
Background: Oral SCC is a complex malignancy where environmental factors, viral infections and genetic alterations most likely interact, and thus give rise to the malignant condition. The HSP70 play a direct role in apoptosis inhibition by aligning the improved integrity of a cell’s proteins with the improved chances of that particular cell’s survival.P21 gene produces p21 protein which is a potent cyclin-dependent kinase inhibitor that plays a significant role in carcinogenesis. The aims of the study were to evaluate and compare the immun-histochemical expression of the HSP70 and cell cycle protein p21in NOM, OED, and OSCC. Correlate both marker expressions with each other.Materials and methods: Forty six formalin-fixed, paraffin embedded tissue blocks(10 cases of normal oral mucosa,16 cases of oral epithelial dysplasia, and 20 cases of oral squamous cell carcinoma) were included in this study, an immunohistochemical staining was performed using antiHSP70monoclonalantibody, and anti p21 monoclonal antibody.Results: Positive IHC expression ofHSP70 was found in 2 cases (20%) of NOM, 13 cases (81.3%) of OED and in 16 cases (85%) of OSCC. Positive IHC expression of P21 was detected In NOM in 2 cases (20%), while it was found in 9 cases (56.2%) of OED, and in 14 cases (70%) of OSCC .The difference between the expressions of both markers was statistically significant in NOM, highly significant in OED, and OSCC.Conclusions: This study signify the important role of HSP70 and p21in oral carcinogenesis and in the evolution of the mucosa from normal to dysplastic to invasive carcinoma